THE EFFECTIVENESS OF PICTURES IN TEACHING REGULAR AND IRREGULAR NOUNS OF STUDENTS’ ACHIEVEMENT IN WRITING AT SEVENTH GRADE OF SMP NEGERI 4 PEMATANG SIANTAR - Anni Sepriana Saragih Sidauruk; Christian Neni Purba; Novra Melisa P. Hutabarat (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research was carried out to find whether or not the effectiveness of pictures on students’understanding of regular and irregular nouns at grade seven of SMP Negeri 4 Pematang Siantar. The research methodology used in this research was a quasi-experimental design. there were two classes taken as the sample of this research, class VII-6 as the experimental class and class VII-5 as the control class. The research was collected by administering pre-test and post-test. The research findings showed that there was significant effectiveness by using pictures in teaching regular and irregular nouns of students’ achievement in writing. It can be seen from the testing hypothesis, it showed that the ttest value (4,02) was higher than the ttable value (1,92) at level of significance 5% with degree of freedom (df) was 58. This were by the score of post-test score in experimental class was 75,50 was higher than the average post-test score in control class which was 68,66. The research can be concluded that using pictures on students’ understanding regular and irregular nouns is very effective for students’ achievement in writing at seventh grade of SMP Negeri 4 Pematang Siantar.